EXAMINING BRAIN TISSUE OXYGEN LEVELS AND METABOLIC ACTIVITY IN FOCAL AND DIFFUSE TRAUMATIC BRAIN INJURY: A CROSS-SECTIONAL STUDY. - Hashmi, Md Mohsin (Student’s Journal of Health Research Africa, 2024)
Background: The study aimed to determine if the response pattern varied based on the type of injury and probe location by examining cerebral metabolism and oxygen levels using microdialysis (MD) and the novel near-infrared spectroscopy (NIRS) probe. Methods: The cross-sectional study included twenty Traumatic Brain Injury (TBI) patients with a Glasgow Coma Scale score of ≤8 was included. Advanced neuromonitoring techniques, including microdialysis and brain tissue oxygenation monitoring, were employed to assess cerebral metabolism and oxygen levels. Statistical analysis involved mean, standard deviations, ANOVA, and Mann–Whitney U test. Results: The study included 20 TBI patients (mean age 45 ± 10 years, predominantly male). Mean intracranial pressure (ICP) was 18.5 ± 4.2 mmHg, and cerebral perfusion pressure (CPP) was 65.2 ± 5.8 mmHg. Brain tissue oxygenation (BtipO2) averaged 22.6 ± 3.5 mmHg. Significant differences in BtipO2 were found between focal (25.0 ± 3.0 mmHg) and diffuse TBI (18.0 ± 2.5 mmHg) (p < 0.05). Higher BtipO2 was observed with ICP < 20 mmHg and CPP > 60 mmHg. Microdialysis showed varying levels of lactate (4.2 ± 1.0 mmol/L), pyruvate (1.8 ± 0.5 mmol/L), glucose (2.5 ± 0.7 mmol/L), glutamate (10.3 ± 2.2 μmol/L), and glycerol (0.6 ± 0.3 μmol/L). Further Mann-Whitney U tests showed notable BtipO2 fluctuations at specific intervals. Conclusion: Comprehensive monitoring of intracranial parameters and cerebral metabolism provides crucial insights for TBI management. Tailored treatment strategies guided by advanced neuromonitoring techniques can improve patient outcomes by addressing brain tissue vulnerability and metabolic disturbances. Recommendations: It is recommended to integrate advanced neuromonitoring techniques into routine TBI management protocols. Personalized treatment approaches based on individual patient profiles should be implemented.